PERKEBUNAN KELAPA SAWIT INDONESIA DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN - Jan Horas V. Purba; Tungkot Sipayung (Masyarakat Indonesia, 2017)
The purpose of this study is to analyze (1) whether oil palm plantations are the main drivers of deforestation in Indonesia; and (2) how does the Indonesian palm oil industry contribute to sustainable development both economically, socially and ecologically. Oil palm plantations are Indonesia’s strategic industries. Since 2000, the Indonesian palm oil industry has grown rapidly and has influenced the dynamics of competition among vegetable oils including the form of black campaigns and accusations as drivers of deforestation in Indonesia. The researchmethodology is empirical descriptive research, which are: (1) to analyze the history of deforestation in logging era in Indonesia and related to the development of oil palm plantation and (2) to analyze the linkage of Indonesian oil palm plantation development with economic, social and ecological aspect. In the period 1950-2013, conversion of forests into non-forests is quite high ie 98.8 million hectares. However, the area of oil palm plantation Indonesia only increased from 0.1 million hectares (1950) to 10.4 million hectares (2013). Based on satellite data (Gunarso, et al., 2012) revealed that the origins of Indonesian oil palm plantations are mostly from degraded land, and only 3.4 percent are converted from primary forest. This proves that oil palm plantations as the main drivers of deforestation in Indonesia are not true. In the economic aspect, the palm oil industry contributes in generating foreign exchange, regional development and successfully creating farmers into middle income. In the social aspect, the oil industry plays a role in rural development and poverty reduction and equitable economic development, and improves income and development inequalities. In the ecological aspect, oil palm plantations contribute to sustainable development through its role in absorbing CO2 and generating O2, and increasing land biomass. Oil palm plantations also reduce greenhouse gas emissions. Keywords: multifunctional agriculture, sustainable, economic, social, ecologicalABSTRAKTujuan penelitian ini adalah menganalisis (1) apakah perkebunan kelapa sawit merupakan pemicu utama deforestasi di Indonesia; dan (2) bagaimanakah kontribusi industri minyak sawit Indonesia terhadap pembangunan berkelanjutan, baik secara ekonomi, sosial, maupun ekologi. Perkebunan kelapa sawit merupakan industri strategis Indonesia. Sejak 2000, industri minyak sawit Indonesia berkembang pesat dan memengaruhi dinamika persaingan antar minyak nabati termasuk bentuk kampanye hitam dan tuduhan sebagai pemicu deforestasi di Indonesia. Metodologi penelitian adalah penelitian deskriptif empiris, yakni: (1) untuk menganalisis sejarah deforestasi pada era logging di Indonesia dan dikaitkan dengan perkembangan perkebunan kelapa sawit; serta (2) menganalisis keterkaitan pembangunan perkebunan kelapa sawit Indonesia dengan aspek ekonomi, sosial, dan ekologi. Pada  1950–2013, konversi hutan menjadi nonhutan cukup tinggi, yakni 98,8 juta hektare. Namun, luas perkebunan kelapa sawit Indonesia hanya meningkat dari 0,1 juta ha (1950) menjadi 10,4 juta ha (2013). Citra satelit (Gunarso dkk., 2012) mengungkapkan bahwa asal-usul lahan perkebunan kelapa sawit Indonesia sebagian besar berasal dari lahan telantar (degraded land), konversi lahan pertanian, dan hanya 3,4% yang dikonversi dari hutan primer. Hal ini membuktikan anggapan bahwa perkebunan kelapa sawit sebagai pemicu utama deforestasi di Indonesia tidak benar. Dalam aspek ekonomi, industri minyak sawit berkontribusi pada pembangunan berkelanjutan, menghasilkan devisa, pembangunan daerah, dan berhasil menciptakan petani ke berpendapatan menengah. Perkembangan industri minyak sawit juga bersifat inklusif dan menarik perkembangan sektor-sektor lain. Dalam aspek sosial, industri minyak berperan dalam pembangunan pedesaan, pengurangan kemiskinan, pemerataan pembangunan  ekonomi, serta memperbaiki ketimpangan pendapatan dan pembangunan. Dalam aspek ekologi, perkebunan sawit menyumbang pada pembangunan berkelanjutan melalui peranannya dalam menyerap CO2 dan menghasilkan O2 serta meningkatkan biomassa lahan. Perkebunan kelapa sawit juga mengurangi emisi gas rumah kaca.Kata kunci: multifungsi pertanian, berkelanjutan, ekonomi, sosial, ekologi